2012
DOI: 10.1007/s10856-012-4664-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive hydrogel of hydrophobically-modified methylcellulose for intravaginal drug delivery

Abstract: Hydrogels with the advantages of prolonging drug release and administration convenience are necessary for intravaginal drug delivery to prevent sexual transmission of human immunodeficiency virus and other vaginal infections. In this study, the thermosensitive hydrogel of methylcellulose modified by stearic acid (MCS) were evaluated in the presence of NaCl and phosphates, which exhibited sol-to-gel transition performance at body temperature or even lower. The in vitro cytotoxicity and in vivo mucosal irritatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…The irritation of LDH-P407 gel to rabbit vagina mucosa was studied compared with 0.9% normal saline, P407 gel and nonoxinol gel (Figure 3). After HE staining, the mucosal structure remained intact in the saline group, at the same time, in the LDH-P407 group, P407 group and nonoxinol group, the vaginal epithelium was little loose but almost no oedema, bleeding or neutrophil infiltration occurred [12]. The immunohistochemical results showed that there were less inflammatory cytokines of TNF-a and IL-6 in the saline group, P407 group and LDH-P407 gel group than in the nonoxinol gel group.…”
Section: Irritation Assessment Of the Gel To Cervicovaginal Mucosamentioning
confidence: 85%
See 1 more Smart Citation
“…The irritation of LDH-P407 gel to rabbit vagina mucosa was studied compared with 0.9% normal saline, P407 gel and nonoxinol gel (Figure 3). After HE staining, the mucosal structure remained intact in the saline group, at the same time, in the LDH-P407 group, P407 group and nonoxinol group, the vaginal epithelium was little loose but almost no oedema, bleeding or neutrophil infiltration occurred [12]. The immunohistochemical results showed that there were less inflammatory cytokines of TNF-a and IL-6 in the saline group, P407 group and LDH-P407 gel group than in the nonoxinol gel group.…”
Section: Irritation Assessment Of the Gel To Cervicovaginal Mucosamentioning
confidence: 85%
“…Microbicides based on hydrogel hold a promising application in the vaginal/rectal drug delivery system due to its convenient administration and good controlled release effect [3,10,11]. The thermosensitive hydrogel prepared by hydrophobically modified methylcellulose was reported to show great controlled release of the hydrophilic anti-HIV drug tenofovir for 10 h without burst release [12]. PLGA nanoparticles were reported to load the hydrophobic anti-HIV drug rilpivrine and vaginal topical administration with poloxamer thermosensitive gel, demonstrating that thermo-sensitive gel can significantly reduce the probability of BLT humanized mice infected with HIV-1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-to-gel transition was first determined by the test tube inverting method (Li et al, 2012). The 4 ml vials (diameter 1.1 cm) containing 1 ml of hydrogel solutions were kept in a water bath ranging from 20 C to 36 C, respectively.…”
Section: Thermogelling Properties and Measurement Of Retention Of Hydmentioning
confidence: 99%
“…Ma et al encapsulated camptothecin in the micelles formed by Pluronic F‐127 in an aqueous solution and then obtained a hydrophobic‐drug‐loaded hydrogel after mixed with α‐cyclodextrin. Li et al prepared a stearic acid‐modified methylcellulose hydrogels for hydrophobic drug loading and prolonged release.…”
Section: Introductionmentioning
confidence: 99%